Limitations of free-form-text diagnostic requisitions as a tool for evaluating adherence to appropriate use criteria for transthoracic echocardiography - Banihashemi, Behnam; Maftoon, Kasra; Chow, Benjamin J W; Bernick, Jordan; Wells, George A; Burwash, Ian G (Université d'Ottawa | University of Ottawa, 2015)
Abstract Background Monitoring the adherence to Appropriateness Use Criteria (AUC) has been identified as an important component for the accreditation of echocardiography laboratories. Referral requisitions are a logical tool to rapidly determine the appropriateness of transthoracic echocardiography (TTE) referrals, however data is lacking. We investigated whether standard free-form-text TTE referral requisitions can be used to evaluate AUC adherence. Methods Consecutive TTE referral requisitions to the University of Ottawa Heart Institute echocardiography laboratory were reviewed over a four-week period. Indication on the requisition was matched with the relevant indication on the 2011 American College of Cardiology Foundation (ACCF) AUC. Requisitions that did not provide sufficient information to identify the relevant AUC indication were identified as inadequate. For inadequate requisitions, reason for the referral was clarified through medical records and referring physicians. Results Of the 1303 requisitions, 26.2% did not provide adequate information to determine adherence to AUC, despite a non-adherence (inappropriate) rate of only 6.1% in the referral population. Indication for referral, physician specialty, outpatient status, and prior echocardiogram were independent predictors of inadequate requisitions (p < 0.001, respectively). The most common reasons for inadequate requisitions were a failure to report: 1) change in clinical status, 2) date of a prior echocardiogram, and 3) type and/or severity of a valve lesion. Inclusion of this information would have decreased the inadequacy rate by 56%. Conclusion In a large, academic echocardiography laboratory, over one quarter of free-form-text TTE requisitions are inadequate to evaluate AUC adherence. Structured requisition formats requiring AUC-relevant information are needed to facilitate the practical application of AUC in the echocardiography laboratory.